SISTEM INFORMASI RAWAT INAP PASIEN PADA RUMAH SAKIT BEDAH MITRA SEHAT DENGAN MENGGUNAKAN VISUAL BASIC - Kemal Farouq Mauladi (Universitas Islam Lamongan, 2017)
Information system patient at hospital of healthy partner surgery is one kind of software that can be used to assist administration process, registration and data processing at one of ins titution which move in public service area. In this research will be made an inpatient information system using Visual Basic programming language. The amount of data and the need for rapid information delivery in the administration of payment services and data collection of patients using information technology as a medium that is considered capable and reliable to assist in data processing and presentation of information fast, easy and accurate.